Immunotherapy in cervical cancer: an innovative approach for better treatment outcomes - Treshita Dey; Sushma Agrawal (Exploration of Targeted Anti-tumor Therapy)
Cervical cancer remains a significant global health challenge, ranking as the fourth most common cancer among women. Persistent infection with high-risk human papillomavirus (HPV) is the primary etiological factor, leading to immune evasion mechanisms that promote tumor development and progression. Immunotherapy has emerged as a transformative approach in the management of cervical cancer, aiming to restore and enhance the body’s immune response against tumor cells. Checkpoint inhibitors targeting programmed death-1 (PD-1) and its ligand (PD-L1) have shown promising results in patients with advanced or recurrent cervical cancer. Pembrolizumab, a PD-1 inhibitor, has been approved for PD-L1-positive cervical cancer, demonstrating durable responses. However, low response rates necessitate exploration of combination strategies. Trials are underway combining checkpoint inhibitors with chemotherapy, radiation, or other immunotherapeutic agents to enhance efficacy. Therapeutic vaccines targeting HPV antigens, such as E6 and E7 oncoproteins, are also a focus of active research. These vaccines aim to elicit robust cytotoxic T-cell responses, offering a potential strategy for early intervention and disease control. Adoptive T-cell therapies, including engineered T-cell receptor (TCR) and chimeric antigen receptor (CAR)-T cells, represent cutting-edge advancements, though challenges with tumor heterogeneity and off-target effects persist. However, challenges such as limited response rates and immune evasion mechanisms remain. The tumor microenvironment (TME) in cervical cancer, characterized by immunosuppressive cells and cytokines, poses a significant barrier to effective immunotherapy. Emerging approaches targeting the TME, such as cytokine modulation, hold promise in overcoming resistance mechanisms. Key gaps include a lack of biomarkers for patient selection, insufficient understanding of TME dynamics, and suboptimal strategies for overcoming antigen heterogeneity and immune resistance. This review addresses these issues by providing a comprehensive analysis of the current landscape of cervical cancer immunotherapy, identifying critical barriers, and highlighting emerging approaches, such as combination therapies, novel immune targets, and strategies to modulate the TME, to guide future research and clinical practice.